Effective blood glucose control in Chinese children with type 1 diabetes via a do-it-yourself artificial pancreas system: a single-center study - Lihong Yang; Fei Xie; Linqi Han; Fengyan You; Zhiqiang Wei; Caihong Liu; Chao Xu; Yan Sun (Therapeutic Advances in Endocrinology and Metabolism)
Background/purpose: The artificial pancreas system is among the most advanced devices for blood glucose management and is known to improve patients’ glycated hemoglobin levels and time spent within the target glucose range. However, the use of an artificial pancreas in children with type 1 diabetes (T1D) in China has not yet been reported. Methods: A retrospective study was conducted involving patients diagnosed with T1D who used a do-it-yourself artificial pancreas system (DIYAPS). The main inclusion criteria were as follows: T1D diagnosis, age between 3 and 18 years, usage of an insulin pump, and continuous glucose monitoring records for at least 3 months. The exclusion criterion was any comorbid conditions that could interfere with the study. The primary outcomes measured were changes in hemoglobin A1c (HbA1c) and time in range (TIR) before and after the DIYAPS was used. Results: A total of 41 people were included in the study, including 21 males and 20 females, with a mean age of 9.4 years (standard deviation: 2.9 years), a median duration of T1D of 1.5 years (1.1–2.3), and a median duration of insulin pump use of 1.1 years (0.8–1.7). Compared with the baseline period (pre-DIYAPS), after using a DIYAPS, the TIR increased from 72.4% (57.9–82.4) to 80.8% (73.6–87.5; p  < 0.01), the TAR (>10 mmol/L) decreased from 16.0% (8.2–21.2) to 8.8% (5.2–14.4; p  < 0.01), the fasting blood glucose decreased from 8.2 mmol/L (7.2–9.4) to 6.7 mmol/L (6.3–7.6; p  < 0.01), and the HbA1c decreased from 6.6% (6.1–7.6) to 6.3% (5.9–6.9; p  < 0.05). No diabetic ketoacidosis, severe hypoglycemia, or other adverse events occurred during the use of the DIYAPS. Conclusion: DIYAPS is safe and effective in Chinese children with T1D, particularly in improving TIR.